INTERNATIONAL TRENDS IN THE DEVELOPMENT OF INNOVATIVE HR TECHNOLOGIES IN THE CONTEXT OF THE DIGITAL ECONOMY - PYSAREVSKA, Hanna; PYSAREVSKYI, Mykola; MUKHA, Danylo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The aim of the article is to analyze international trends in the development of innovative HR-technologies and to assess their impact on personnel management efficiency within the context of the digital economy. The study employs a combination of research methods, including system analysis, comparison and synthesis, as well as a structural-functional approach, to examine the adoption, integration, and effectiveness of digital HR solutions across diverse organizational and cultural environments. The findings demonstrate that the implementation of digital HR platforms, advanced data analytics, online learning tools, and automation of administrative HR processes significantly enhances workforce productivity, fosters the formation of agile and adaptive teams, and strengthens the strategic responsiveness of organizations in rapidly changing market conditions.The scientific novelty of the research lies in the systematic synthesis of global best practices and innovative HR models, highlighting the role of digital HR technologies as key drivers of organizational competitiveness, employee engagement, and continuous performance improvement. The study also emphasizes the importance of aligning HR digitalization strategies with overall corporate digital transformation initiatives, ensuring that technological adoption is accompanied by appropriate organizational, cultural, and managerial adjustments. Moreover, the research identifies critical success factors for international HR technology implementation, including leadership support, data-driven decision-making, employee digital literacy, and integration with other business functions.The practical significance of the study is reflected in its potential to guide managers and HR professionals in leveraging international experience for optimizing personnel management practices, enhancing employee development, and promoting innovation within organizations. The article provides actionable insights for adopting emerging HR tools, including AI-based recruitment and performance evaluation systems, cloud-based collaboration platforms, and predictive analytics for talent management. By examining trends across different countries and industries, the study offers a comprehensive framework for organizations seeking to achieve sustainable growth, improve workforce adaptability, and maintain a competitive edge in the digital economy.
Keywords: HR technologies; digital economy; digital transformation; human resource management; innovations; data analytics; agile teams; international practices; competitiveness